Claims of Economic Rights of Wives in Divorce Cases According to the Compilation of Islamic Law in the Biak Religious Court Islamic Family Law - Muhammad Taufiq Torano; Faisal; Hendra Yulia Rahman (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study used a qualitative type of legal research. His approach is through Normative Theological, Juridical Normative and Sociological approaches. Data collection techniques through interviews and documentation. Data processing and analysis techniques use qualitative methods. The way the wife claims her economic rights (Mut'ah, Nafkah iddah and Nafkah Madhiyah) in divorce cases in the Biak Religious Court is cumulated in divorce cases or reconvention lawsuits are filed in talaq divorce cases. Especially for Hadhanah cases, a separate child custody lawsuit can be filed. Factors that prevent the wife from being able to prosecute her optimally in the Biak Religious Court are caused by 3 things, namely: The ability of the husband because he does not work, the wife's demands are too high because the wife's lifestyle / prestige is high and there is no evidence of letters or witnesses explaining the amount of the husband's income so that the husband's income cannot be proven by the wife. The impact of the wife's unfulfilled economic rights is that the husband's arbitrariness occurs and is very detrimental to the wife in undergoing the mass of iddah because she is burdened with the necessities of life. ?